Licensing a common value innovation when signaling strength may backfire - Cuihong Fan; Byoung Heon Jun; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
This paper reconsiders the licensing of a common value innovation to a downstream duopoly, assuming a dual licensing scheme that combines a first-price license auction with royalty contracts for losers. Prior to bidding firms observe imperfect signals of the expected cost reduction; after the auction the winning bid is made public. Bidders may signal strength to their rivals through aggressive bidding, which may however backfire and mislead the innovator to set an excessively high royalty rate. We provide sufficient conditions for existence of monotone bidding strategies and for the profitability of combining auctions and royalty contracts for losers.
urn:nbn:de:bvb:19-epub-13262-4
Keywords: D21; D43; D44; D45; 330; Patents; licensing; auctions; royalty; innovation; R&D; mechanism design; Innovation; Lizenz; Auktionstheorie; Nutzungsentgelt; Industrieforschung; Mechanismus-Design-Theorie; Theorie